Information from Inaction: Vested Options Unexercised and Firm Performance - Bui, Dien Giau; Lin, Chih-Yung; Lin, Tse-Chun (The Review of Asset Pricing Studies, 2026)
We hypothesize that when managers do not exercise their options, they signal valuable private information. Accordingly, we construct a proxy to capture managers’ private information from their in-the-money vested options unexercised (VOU) and find that high VOU firms’ stocks are underpriced. A long-short portfolio based on VOU generates a 5% alpha annually. Additionally, we find a positive relation with subsequent operating performance. Firms with higher VOU also receive more favorable analyst recommendations and upgraded credit ratings. Firms with higher VOU are more likely to issue news releases, share repurchases, and stock splits to convey that private information to the public. (JEL G11, G14, G32, G35, G40)